A Folkloric Study On Wide Sargasso Sea - Uzun, Esra (East Carolina University, 2011)
This study aims to offer an alternative approach to analyze and understand literary texts through folklore. I focused on Jean Rhys's famous novel Wide Sargasso Sea, which has often been examined through a postcolonial approach. My thesis suggests that the postcolonial criticisms are limiting to our understanding of the novel; therefore, an alternative way is needed to explore Wide Sargasso Sea and evaluate its major themes such as cultural clashes and misconceptions from a different perspective. Folklore has allowed me to explore the novel from a wider spectrum because it provides a deeper understanding of the characters, their identities, places, and dreams in the novel. Folklore not only studies the individuals and their societies, but also goes beyond the stereotypes and generalizations.
Keywords: Folklore; Caribbean literature; British and Irish literature; Colonialism and postcolonialism; Dreams; Gender and stereotypes; Identity and cultural misconceptions; Sense of place; Wide Sargasso Sea; Rhys, Jean. Wide Sargasso Sea--Criticism and interpretation; Literature and folklore; Caribbean literature--Colonial influence